(untitled) (e-Journal of Linguistics, 2019)
This study aims to find the functions and ideologies of Depeha Village folklore entitled Sang Sandiaka. The focus of the problems to be studied in this study consists of three things; they are: (1) to find out the narrative structure of the folklore of Sang Sandiaka, (2) to find out the functions of the story, and (3) to find out the ideologies in it. The type of this study is qualitative. The theories used in this study are the morphological theory , the function theory and the mythological theory. The data were collected through documentation and interview. Thus the analysis started with a review of Sang Sandiaka’s story, then the narrative structure and the function as well as the meaning of the story, and the ideologies contained in it were presented. The results of this study showed that: (1) the story of Sang Sandiaka functions to remind the past, as non-formal education of the community and as the entertainment for the Depeha Village community, and (2) the ideologies which the folklore contain are the ideology of leadership and the ideology of social equality.